Finite element analysis of a lightweight box structure / Mohd Amir Bohari - Bohari, Mohd Amir (2003)
A lightweight box with dimension of 1200mm x 400mm x 120mm consisting of 4 ribs, 8 stringers and 2 spar webs was designed and fabricated. The structural behaviors were studied in terms of stress and deflection by theoretical and Finite Element Analysis (FEA). FEA analysis was carried out based on 116 Elements consisting of 60 Shell41 type (for skin and ribs), 8 shell28 (for spar webs), and 48 link8 type (for stringer and spar flank). The structural integrity was tested by measuring the strain of 4 strain and rosette gauges at 5 different locations. The stress values from the theoretical and FEA are in good agreement. Experimental results showed good agreement with the predicted values at locations 1, 3 and 5. However the experimental stresses at location 2 and 4 are deviated by 43 and 84% respectively from the predicted values. Such high deviations indicate a local effect, since location 2 is closed to the rivet and 4 are on the stringer. Meanwhile, location 1 and 3 are on the skin and 5 was the rosette at the web. The experimental deflection values at all loads are significantly deviated from.the predicted values. Therefore the theoretical approach has got to be modified by taking several factors such as the effect of the rivet on the geometry and fabrication imperfection into consideration. The experimental values are higher than the predicted values.